Computer‐Assisted Design of Sustainable Syntheses of Pharmaceuticals and Agrochemicals from Industrial Wastes. Issue 19 (25th August 2022) - Le Pogam, Pierre; Papon, Nicolas; Beniddir, Mehdi A.; Courdavault, Vincent
Abstract: Computer‐based strategies vastly enhanced the field of analytical chemistry. The impact of data‐driven technologies in shaping organic chemistry strategies long remained comparatively elusive but various tools recently emerged to computationally plan multistep organic syntheses. A recent study elegantly takes benefit of an in‐house library of chemical reactions enriched with various metadata to provide numerous, reliable and realistic organic chemistry workflows to structurally‐varied drugs of interest, from locally available industrial by‐products. The retrieval of the different synthetic pathways and a scoring based on different features, especially comprising sustainability considerations, are also proposed. Abstract : Repurposing waste chemicals : An efficient and predictive approach of by‐product repurposing has been recently developed through a computational synthesis‐based strategy mapping the network of molecules synthesizable from the most common waste chemicals up to valuable compounds. This waste‐to‐drug synthetic strategy thus foreshadows future sustainable productions based on the circular chemistry concept.